2019
DOI: 10.1007/s13139-018-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Recommendations for Lymphoscintigraphy in the Diagnosis of Peripheral Lymphedema: the Genoa Protocol

Abstract: Introduction Lymphoscintigraphy is the gold standard for imaging in the diagnosis of peripheral lymphedema. However, there are no clear guidelines to standardize usage across centers, and as such, large variability exists. The aim of this perspectives paper is to draw upon the knowledge and extensive experience of lymphoscintigraphy here in Genoa, Italy, from our center of excellence in the assessment and treatment of lymphatic disorders for over 30 years to provide general guidelines for nuclear medicine spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The postoperative elastic compression is required immediately after MLVA and up to 12 months because pathological findings (Boccardo, Fulcheri, et al, 2013) have shown how in lymphedema, the lymphatic collector pathways tend to lose the elastic component of the wall, losing more or less markedly the lymphatic pump capacity, and lymphoscintigraphy has demonstrated this aspect from a functional point of view. After 12 months, this functional capacity partially recovers and this aspect is demonstrated by the clinical stability of the lymphedema and by lymphoscintigraphic studies (Villa et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The postoperative elastic compression is required immediately after MLVA and up to 12 months because pathological findings (Boccardo, Fulcheri, et al, 2013) have shown how in lymphedema, the lymphatic collector pathways tend to lose the elastic component of the wall, losing more or less markedly the lymphatic pump capacity, and lymphoscintigraphy has demonstrated this aspect from a functional point of view. After 12 months, this functional capacity partially recovers and this aspect is demonstrated by the clinical stability of the lymphedema and by lymphoscintigraphic studies (Villa et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Lymphoscintigraphy is able to demonstrate the flow of lymph in both the superficial and deep lymphatic pathways and it has been shown to have high sensitivity (96%) and specificity (100%) for lymphedema (Villa et al, 2019). Lymphoscintigraphy and the interpretation of results should be done by the same nuclear physician using the same device and the same protocol, to avoid possible wrong assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial and deep collectors are functionally complementary, and the deep compartment may participate in lymph drainage of the skin. 28,29 In our center, we adopted the rest/stress intradermal lymphoscintigraphy. This method was instituted in collaboration with our surgeons and physiotherapists to evaluate patients with lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…Microsurgical approach is planned on the guide of preoperative superfi cial and deep lymphoscintigraphy, combined with calculation of Transport Index [16][17][18].…”
Section: Introductionmentioning
confidence: 99%